Implementasi Islam Progresif pada Permendikbud Ristek No. 30 Tahun 2021 dalam Kajian Filsafat Hukum Islam - Busyro, Busyro; Alwana, Hanif Aidhil; Arsal, Arsal; Shafra, Shafra; Basir, Gusril (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
Regulation issued by the Ministry of Research, Technology and Higher Education Number 30 of 2021 about prevention and handling of sexual violence in campus has raised pros and cons among Indonesian Muslims because several articles allegedly provide sexual freedom on campus with an editorial “except with the victim consent”. The editorial seems to strongly prioritize one of the principles of Progressive Islam activists; on the other hand, there are philosophical values of the Islamic law that are not realized, especially in protecting dignity and heredity (hifz al-nasb). This study aims to reveal the implementation of progressive Islam in the regulation, and then the realization of progressive Islam will also be seen from the philosophical point of view of Islamic law. This research is qualitative by using data from library research. The results of the study indicate that the Ministerial Regulation has implemented one of the progressive Islamic concepts by prioritizing international human rights as the rationale, and the implementation of progressive Islam that relies on international human rights is not in line with the philosophy of Islamic law which highly upholds the protection of dignity and heredity (hifz al-nasb) from the side of maslahah al-hajiya. Therefore, the editorial must be changed, in order to achieve the benefit of the world and the hereafter for Indonesian Muslims.